Clinical Risk Factors for Central Line-Associated Venous Thrombosis in Children - Shah, Samir H.; West, Alina Nico; Sepanski, Robert J.; Hannah, Debbie; May, William N.; Anand, Kanwaljeet J. S. (Frontiers in Pediatrics, 2015)
ABSTRACT Background: Identifying risk factors related to Central Venous Line (CVL) placement could potentially minimize Central Line-Associated Venous Thrombosis (CLAVT). We sought to identify the clinical factors associated with CLAVT in children. Methods: Over a 3-year period, 3,733 CVLs were placed at a tertiary-care children’s hospital. Data were extracted from the electronic medical records of patients with clinical signs and symptoms of venous thromboembolism (VTE), diagnosed using Doppler ultrasonography and/or echocardiography. Statistical analyses examined differences in CLAVT occurrence between groups based on patient and CVL characteristics (type, brand, placement site, and hospital unit). Results: Femoral CVL placement was associated with greater risk for developing CLAVT (OR 11.1, 95% CI 3.9-31.6, p<0.0001). CVLs placed in the NICU were also associated with increased CLAVT occurrence (OR 5.3, 95% CI 2.1-13.2, p=0.0003). CVL brand was also significantly associated with risk of CLAVT events. Conclusion: Retrospective analyses identified femoral CVL placement and catheter type as independent risk factors for CLAVT, suggesting increased risks due to mechanical reasons. Placement of CVLs in the NICU also led to an increased risk of CLAVT, suggesting that small infants are at increased risk of thrombotic events. Alternative strategies for CVL placement, thromboprophylaxis, and earlier diagnosis may be important for reducing CLAVT events.